Growth vs. value: The effect of the COVID-19 pandemic - Barbara Rasiova (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
Growth and value are popular terms in the lexicon of finance. For many years, scholars and investment professionals have claimed that value strategies outperform the growth ones, even in major market declines. However, since the early 2010's, this seems to no longer hold, as growth strategies consistently generate superior returns. With declaration of Covid-19 as a pandemic, stock markets across the world were confronted with immense uncertainty. Taking the recent trend reversal in outperformance into consideration, such economic climate sparks interest in the differences in the response of growth and value strategies. Using log returns data for value and growth portfolios during the 2010-2021 period, this study provides empirical evidence that value portfolios show greater sensitivity to the Covid-19 pandemic. While findings show that the pandemic had a profound impact on the performance and riskiness of both portfolios, they clearly indicate higher volatility, frequency of extreme losses and average loss in the value portfolio, which further extends the growth outperformance to market downturns.
Keywords: G1; G11; G14; 330; Value; Growth; Pandemic; Return; Risk